2018
DOI: 10.5009/gnl17140
|View full text |Cite
|
Sign up to set email alerts
|

Slow-Pull Using a Fanning Technique Is More Useful Than the Standard Suction Technique in EUS-Guided Fine Needle Aspiration in Pancreatic Masses

Abstract: Background/AimsEndoscopic ultrasound-guided fine needle aspiration (EUS-FNA) is useful for obtaining pancreatic mass samples. The combination of modified techniques (i.e., slow-pull technique and fanning technique) may improve the quality of the sample obtained by EUS-FNA. We investigated the effectiveness of a combined slow-pull fanning technique in EUS-FNA for pancreatic mass.MethodsThis prospective comparative study investigated EUS-FNA performed for pancreatic solid masses between August 2015 and July 2016… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 28 publications
0
53
0
Order By: Relevance
“…▶ Table 1 summarizes the characteristics of the seven included studies [10,11,[17][18][19][20][21]. They were all full-text RCTs published between 2017 and 2019; two were initially available only as abstracts from conferences' proceedings at the time of submission that during the revision process became available as full text and whose data were accordingly updated [20,21].…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…▶ Table 1 summarizes the characteristics of the seven included studies [10,11,[17][18][19][20][21]. They were all full-text RCTs published between 2017 and 2019; two were initially available only as abstracts from conferences' proceedings at the time of submission that during the revision process became available as full text and whose data were accordingly updated [20,21].…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…Only two studies [10,20] were multicentric. Two studies were carried out in the US [10,11], 2 in Korea [18,19] and one each in Brazil [21], India [17] and Italy [20]. Different needles were employed, with 3 studies employing FNB needles [11,19,20] and 4 FNA [10,17,18,21]).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…16 Lee and colleagues also found that the slow-pull capillary technique had a higher diagnostic yield than the suction technique in pancreatic disease. 17 Although the slow-pull capillary technique is increasingly being used for the diagnosis of digestive diseases, there is currently no evidence regarding its use in respiratory diseases. Therefore, the aim of this study was to compare the diagnostic accuracy of EBUS-TBNA using the suction technique and the slow-pull capillary technique.…”
Section: Introductionmentioning
confidence: 99%